Endogenous and exogenous teeth whitening through gel-based bleaching hydrogen peroxide (35%) with the aid of silicon guide - Amaral, Fabrício Reskalla [UNESP]; Pinheiro, Marília Caldonazzo [UNESP]; Piccioni, Mayra Andressa Rodrigues Valinhos I. [UNESP]; Rabelo Caldas, Marília Reagaldo Galvão [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Saad, José Roberto Cury [UNESP]; Porto Neto, Sizenando de Toledo [UNESP] (My University, 2012)
The aim of this study is to demonstrate through a case report, a proposed treatment for discolored teeth, with and without pulp vitality, by the technique of external and internal tooth bleaching with hydrogen peroxide to 35% Lase Peroxide Sensy (DMC) using Whitening Lase II Device (DMC), and a silicone guide (3M ESPE) in the palatine portion of the upper teeth. In this clinical case, the patient had darkened dental elements 11 and 22, and dissatisfaction with the coloring of other elements. It was observed that the techniques used and the materials chosen allowed for an excellent aesthetic result, with technical simplicity and low cost, and minimal occurrence of signs and symptoms
Keywords: Dental bleaching; Hydrogen peroxide; Silicon